2013
DOI: 10.1159/000351034
|View full text |Cite
|
Sign up to set email alerts
|

The CD1d-Natural Killer T Cell Axis in Atherosclerosis

Abstract: A key role for ‘lipid-sensing' CD1-restricted natural killer T (NKT) cells in the pathogenesis of atherosclerosis has been suggested. However, the biology of NKT cells remains poorly characterized, as in different experimental settings their activation was reported to both stimulate and suppress innate and adaptive immune responses. Most of the data from experimental models suggest that NKT cells are proatherogenic; however, it is debated whether the increase in atherosclerosis observed following NKT cell stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…For example, NKT cells promote the immune response to tumours and microbial infections, while suppressing immune responses in autoimmune diseases such as acute hepatitis and arthritis 21 22 23 . Furthermore, NKT cell activation can be harmful to the host in some inflammatory diseases such as atherosclerosis 24 . Despite their paradoxical functions in different disease conditions, NKT cells clearly play a crucial role in regulating the pathogenesis of various diseases.…”
mentioning
confidence: 99%
“…For example, NKT cells promote the immune response to tumours and microbial infections, while suppressing immune responses in autoimmune diseases such as acute hepatitis and arthritis 21 22 23 . Furthermore, NKT cell activation can be harmful to the host in some inflammatory diseases such as atherosclerosis 24 . Despite their paradoxical functions in different disease conditions, NKT cells clearly play a crucial role in regulating the pathogenesis of various diseases.…”
mentioning
confidence: 99%
“…273 The iNKT cells, similar to CD8 + T cells, can express cytotoxic proteins such as granzyme and perforin. 274 Most researches performed on mice indicated that iNKT cells play a pro-atherogenic role. 275 The iNKT cells can activate immune cells in plaque, by secreting cytokines and promoting atherosclerosis development.…”
Section: The Role Of Natural Killer T (Nkt) Cells In Atherosclerosismentioning
confidence: 99%
“…7 Adaptive immunity is further divided into (1) humoral immunity, which is mediated by B cells and antibodies; and (2) cellmediated immunity, which is mediated by T cells that activate macrophages for killing or that lyse infected cells. 15,16 T lymphocytes are characterized by a surface CD3 and consist of two major functional subsets: T-helper (Th) lymphocytes expressing the cell-surface molecule CD4, and cytotoxic T lymphocytes (CTL) expressing the cell-surface molecule CD8. The γ δT cells, however, are another T-cell subset: they have γ δTCR and are negative for CD4 and CD8, and they have CD277 as the antigenpresenting molecule.…”
Section: Immune Disorder Begets Atherosclerotic Cardiovascular Diseasmentioning
confidence: 99%